Primary Pneumatosis Intestinalis of Small Bowel: A Case of a Rare Disease - Daniela Berritto; Raffaello Crincoli; Francesca Iacobellis; Francesca Iasiello; Nunzia Luisa Pizza; Francesco Lassandro; Lanfranco Musto; Roberto Grassi (Case Reports in Surgery)
Pneumatosis intestinalis (PI) is a condition in which multiple gas-filled cysts are located in the bowel wall; it can represent a wide spectrum of diseases and a variety of underlying diagnoses. The present report describes the case of an 86-year-old man with symptomatic primary PI of small bowel treated with surgical approach after periodic episodes of cysts rupture and superimposed inflammation revealed on the basis of a clinical suspicion thanks to abdominal computed tomography. Moreover, after one year of followup, there has been no recurrence of digestive symptoms.